Scalable optical fiber reactor for photocatalytic H2 production: addressing scattering issues - Walko, Priyanka S.; Devi, R. Nandini (International Journal of Hydrogen Energy, 2023)
Scattering is one of the main challenges in scaling up photocatalytic water splitting using the most prevalent powder catalysts. This can be overcome by decoupling the reaction medium from light transmission, as in the case of optical fibers. Here we explore utilizing optical fibers coated with 5 wt% CuO supported on TiO2 for photocatlytic H2 production from water-methanol mixtures. CuO/TiO2 is a well studied photo catalyst in which photoreduced Cu species are known to act as sensitizers for inducing visible light activity. Lower activity of sequentially coated systems indicates that appropriate interfaces of active Cu and TiO2 with water are desirable. The scalability of such optical fiber-based systems along with potential in non-potable turbid water media are demonstrated. Maximum activity of 22 mmoles of H2 in 8 h was obtained with 50 mg of catalyst coated on optical fibers, which increases linearly with increase in fiber numbers, whereas, drastic reduction in activity is observed in powder catalyst upon increasing the catalyst quantity. A one-to-one comparison of 700 mg of catalyst in powder form and coated on optical fibers indicates more than one order enhancement in activity in the optical fiber based system. In addition, -70% retention in activity in highly turbid non-potable water was observed as compared to powdered system which shows complete reduction in the activity by 99.99%. (c) 2023 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: CuO; Optical fibers; photocatalytic water splitting; TiO2; Total internal reflection; Visible light utilisation